Following Jesus : journeys in discipleship : essays in honor of Ronald J. Sider - Alexander, Paul, 1972-; Tizon, Al (Regnum studies in global Christianity., 2013)
What does it mean to follow Jesus in the twenty-first century? The same that it always has: radically and faithfully. Ronald J. Sider and the organization that he founded, Evangelicals for Social Action, are most respected for their pioneering work in the area of evangelical social concern. However, Sider's great contribution to social justice is but a part of a larger vision--namely, biblical discipleship. His works, which span more than four decades, have guided the faithful to be authentic gospel-bearers in ecclesial, cultural, and political arenas. This book honors Ron Sider by bringing together a group of scholar-activists, old and young, to reflect upon the gospel and its radical implications for the twenty-first century. This list includes Craig Keener, Vinay Samuel, Melba Maggay, John Perkins, and Heid Unruh.